(untitled) (Journal of Global Accounting, 2025)
This research examined the impact of ownership structure on the financial performance of listed consumer goods firms in Nigeria. The study adopted a correlational research design and covered a population of twenty-one consumer goods firms listed on the Nigerian Exchange (NGX). From this, a sample of sixteen (16) firms was selected based on the fulfillment of two eligibility criteria over a ten-year period (2015–2024). To analyze the data, the study employed descriptive statistics, correlation analysis, and multiple regression techniques. The findings revealed that ownership structure specifically institutional ownership, managerial ownership, and foreign ownership has an insignificant effect on the financial performance of the selected firms, as measured by Return on Assets (ROA). The results suggest that the structure of firm ownership, while theoretically relevant to corporate governance and performance outcomes, may not be a critical determinant of financial performance within the Nigerian consumer goods sector. This may be due to passive involvement of shareholders, weak enforcement of governance mechanisms, or overriding economic and regulatory constraints affecting firm performance. In light of these findings, it is recommended that the management of listed consumer goods firms in Nigeria should shift focus from mere ownership restructuring and instead invest in strengthening internal corporate governance practices, operational efficiency, managerial accountability, and strategic innovation. Firms should also foster active engagement with shareholders, enhance transparency in financial reporting, and align strategic objectives with long-term value creation. Additionally, policymakers and regulators should support reforms that improve the institutional environment to make ownership mechanisms more impactful in driving firm performance.